The application of whole-exome sequencing in the early diagnosis of rare genetic diseases in children: a study from Southeastern China - Lai, Guihua; Gu, Qiying; Lai, Zhiyong; Chen, Haijun; Chen, Junkun; Huang, Jungao (Frontiers in Pediatrics, 2024)
Background Genetic diseases exhibit significant clinical and genetic diversity, leading to a complex and challenging diagnostic process. Exploiting novel approaches is imperative for the molecular diagnosis of genetic diseases. In this study, we utilized whole-exome sequencing (WES) to facilitate early diagnosis in patients suspected of genetic disorders. Methods This retrospective analysis included 144 patients diagnosed by singleton-WES Trio-WES between January 2021 and December 2023. We investigated the relevance of diagnosis rates with age, clinical presentation, and sample type. Results Among the 144 patients, 61 were diagnosed, yielding an overall diagnostic rate of 42.36%, with Trio-WES demonstrating a significantly higher diagnostic rate of 51.43% (36/70) compared to singleton-WES at 33.78% (25/74) (p < 0.05). Global developmental delay had a diagnosis rate of 67.39%, significantly higher than muscular hypotonia at 30.43% (p < 0.01) among different clinical phenotypic groups. Autosomal dominant disorders accounted for 70.49% (43/61) of positive cases, with autosomal abnormalities being fivefold more prevalent than sex chromosome abnormalities. Notably, sex chromosome abnormalities were more prevalent in males (80%, 8/10). Furthermore, 80.56% (29/36) of pathogenic variants were identified as de novo mutations through Trio-WES. Conclusions These findings highlight the effectiveness of WES in identifying genetic variants, and elucidating the molecular basis of genetic diseases, ultimately enabling early diagnosis in affected children.